Spatial fractionation of phosphorus accumulating biofilm: stratification of polyphosphate accumulation and dissimilatory nitrogen metabolism. Issue 2 (24th March 2022) - Villard, Didrik; Saltnes, Torgeir; Sørensen, Gjermund; Angell, Inga Leena; Eikås, Sondre; Johansen, Wenche; Rudi, Knut
Abstract: The spatial distribution of microorganisms represents a critical issue in understanding biofilm function. The aim of the current work was to develop a method for biofilm fractionation, facilitating the analysis of individual spatial biofilm layers using metagenomic approaches. Phosphorus accumulating biofilm applied in an enhanced biological phosphorus removal wastewater treatment plant, were fractionated, and analyzed. The fractionated biofilm revealed a surprising spatial distribution of bacteria and genes, where potential polyphosphate accumulating organisms account for ∼ 47% of the inner layer microbiome. A spatial distribution of genes involved in dissimilatory nitrogen reduction was observed, indicating that different layers of the biofilm were metabolically active during the anoxic and aerobic zones of the phosphorus removal process. The physical biofilm separation into individual fractions unveiled functional layers of the biofilm, which will be important for future understanding of the phosphorus removal wastewater process.